(untitled) (Polifonia, 2012)
A necessidade de mudança frente ao crescente cenário deavanços tecnológicos solicita ao educador uma postura cada vez maisparticipativa e reflexiva. Temos como tema aqui uma reflexão acercados novos desafios para a formação de professores de inglês que emergemde orientações curriculares com foco no conceito de multiletramento.Tal conceito demanda habilidades necessárias para atuação desse docentena atualidade. A partir das Orientações Curriculares para o EnsinoMédio/Língua Estrangeira– OCEM/LE (BRASIL, 2008), buscou-se umarevisão histórica do conceito de multiletramento, bem como o desenhode uma estrutura conceitual correlacionada. Os desafios do mundo contemporâneodemandam um novo perfil profissional no ensino de línguas.Tais implicações apontam a necessidade de adoção de políticaspúblicas sólidas e estruturantes acompanhadas de melhorias nas condiçõesde trabalho para que seja possível atender às demandas deletramentos da sociedade atual. PALAVRAS-CHAVE: multiletramento, formação de professor, ensino de inglês. MULTILETRACY: NEW CHALLENGES AND PRACTICES IN LANGUAGE IN THE EDUCATION OF TEACHERS OF ENGLISH ABSTRACT : The need for change in times of constant technologicaldevelopment demands the teachers to take an increasingly participativeand reflective stance. In this paper we reflect upon the new challengesthat face English Language Teacher Education that have emerged fromeducational guidelines that focus on the concept of multiliteracy. Suchconcept demands skills needed to be a language teacher today. Byexamining Brazilian’s guidelines to the teaching of foreign languages(BRASIL, 2008), a historical review on the concept of multiliteracy wasdone, as well as the design of a conceptual framework associated withmultiliteracy. Challenges of the contemporary world demand a newprofessional profile in language teaching. These implications point tothe need of adopting strengthened public policies along with improvingeducators’ work conditions in order to comply with the literacy demandsof today’s society. KEYWORDS: multiliteracy, teacher education, foreign language teaching